The Influence of Service Quality, Discount Promotions, and Facilities on Purchase Intention at Waroeng Paman Mutho - Hasibuan, Dea Aprilla; Pohan, Yuli Arnida (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
This study aims to analyze the influence of service quality, discount promotion, and facilities on purchase intention among consumers at Warung Paman Mutho. The research used a quantitative approach with multiple linear regression analysis. The t-test results show that service quality has a positive and significant effect on purchase intention, discount promotion has no significant effect, and facilities have a negative and significant effect on purchase intention. The F-test results indicate that all three independent variables simultaneously have a significant influence on purchase intention. The Adjusted R Square value of 0.642 indicates that 64.2% of the variation in purchase intention can be explained by the three independent variables used in this study, while the remaining 35.8% is influenced by other factors not examined. These findings imply that business managers should prioritize improving service quality and better understand consumer preferences regarding facilities, while also reassessing the effectiveness of discount promotions to ensure that marketing strategies are implemented more effectively.